A proteomic analysis reveals differential regulation of the σ(S)-dependent yciGFE(katN) locus by YncC and H-NS in Salmonella and Escherichia coli K-12 - Beraud, Mélanie; Kolb, Annie; Monteil, Véronique; D'Alayer, Jacques; Norel, Françoise (Molecular & cellular proteomics, 2010)
The stationary phase sigma factor σ(S) (RpoS) controls a regulon required for general stress resistance of the closely related enterobacteria Salmonella and Escherichia coli. The σ(S)-dependent yncC gene encodes a putative DNA binding regulatory protein. Application of the surface-enhanced laser desorption/ionization-time of flight (SELDI-TOF) ProteinChip technology for proteome profiling of wild-type and mutant strains of Salmonella enterica serovar Typhimurium revealed potential protein targets for YncC regulation, which were identified by mass spectrometry, and subsequently validated. These proteins are encoded by the σ(S)-dependent operon yciGFEkatN and regulation of their expression by YncC operates at the transcriptional level, as demonstrated by gene fusion analyses and by in vitro transcription and DNase I footprinting experiments with purified YncC. The yciGFE genes are present (without katN) in E. coli K-12 but are poorly expressed, compared with the situation in Salmonella. We report that the yciGFE(katN) locus is silenced by the histone-like protein H-NS in both species, but that σ(S) efficiently relieves silencing in Salmonella but not in E. coli K-12. In Salmonella, YncC acts in concert with σ(S) to activate transcription at the yciG promoter (pyciG). When overproduced, YncC also activated σ(S)-dependent transcription at pyciG in E. coli K-12, but solely by countering the negative effect of H-NS. Our results indicate that differences between Salmonella and E. coli K-12, in the architecture of cis-acting regulatory sequences upstream of pyciG, contribute to the differential regulation of the yciGFE(katN) genes by H-NS and YncC in these two enterobacteria. In E. coli, this locus is subject to gene rearrangements and also likely to horizontal gene transfer, consistent with its repression by the xenogeneic silencer H-NS.